Consistency in the flight and visual orientation distances of habituated chacma baboons after an observed leopard predation. Do flight initiation distance methods always measure perceived predation risk? - Andrew T. L. Allan (Wiley, 2021)
Abstract Flight initiation distance (FID) procedures are used to assess the risk perception animals have for threats (e.g., natural predators, hunters), but it is unclear whether these assessments remain meaningful if animals have habituated to certain human stimuli (e.g., researchers, tourists). Our previous work showed that habituated baboons displayed individually distinct and consistent responses to human approaches, a tolerance trait, but it is unknown if the trait is resilient to life‐threatening scenarios. If it were consistent, it would imply FIDs might measure specific human threat perception only and not generalize to other threats such as predators when animals have experienced habituation processes. We used FID procedures to compare baseline responses to the visual orientation distance, FID, and individual tolerance estimates assessed after a leopard predation on an adult male baboon (group member). All variables were consistent despite the predation event, suggesting tolerance to observers was largely unaffected by the predation and FID procedures are unlikely to be generalizable to other threats when habituation has occurred. FID approaches could be an important tool for assessing how humans influence animal behavior across a range of contexts, but careful planning is required to understand the type of stimuli presented.